ID 225 – Stimulating the operculo-insular cortex for pain modulation: Crossed evidence from tDCS and intra-cranial stimulation. Issue 3 (March 2016) - Bradley, C.; Moreau, P.; Perchet, C.; Lelekov-Boissard, T.; Isnard, J.; Garcia-Larrea, L.
Abstract : Motor cortex stimulation for pain relief has shown its usefulness but also its limits. In the search for new targets, one can stimulate relatively high (e.g. DLPFC) or low level cortical areas. The posterior insula-medial operculum is one of the earliest areas to process nociceptive information but is a difficult target. We addressed its stimulation along two experimental lines: tDCS and intra-cranial stimulation. Methods: (a) 10 epileptic patients, implanted with intra-cranial electrodes, received high-frequency stimulation at operculo-insular contacts. 10 supra-threshold peripheral painful electrical stimuli were delivered before, during and after low-frequency cortical stimulation between two neighboring contacts. (b) A multi-polar tDCS montage was used to deliver anodal and cathodal stimulation to the right operculum-insula of 10 healthy participants, in a double-blind cross-over design. Subjective pain threshold and tolerance to a Cold Pressor Test, vegetative responses and EEG were compared before, during and after the application of tDCS. Results: (a) Neither perception nor intracranially-recorded evoked potentials to a nociceptive stimulus were significantly altered by low-frequency, low-intensity intracranial stimulation of operculum-insula. (b) While pain thresholds were not significantly modulated by multi-polar tDCS, there was a differential effect of polarity on pain tolerance, with cathodal stimulation leading to faster hand withdrawal. Work carries on!